2016
DOI: 10.1515/folmed-2016-0027
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between visual field changes and optical coherence tomography measurements in advanced open-angle glaucoma

Abstract: Aim: To assess relationships between functional changes in visual field and structural changes in advanced open-angle glaucoma (OAG) found using spectral-domain optical coherence tomography (SD-OCT). Methods: Thirty-one eyes of 25 patients with OAG were included in this study. Besides the routine ophthalmological exam the patients underwent standard automated perimetry (SAP) (Humphrey Field Analyzer) and SD-OCT (RTVue–100) performed within 6 months. The global perimetric indices in the study group were as foll… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…Changes in ONH parameters, such as the rim area and C:D ratio (average and vertical), were small but statistically significant in advanced glaucoma [15]. Kostianeva et al [45] found significant correlations of the rim area and C:D ratio with the HFA 30-2 VF MD in advanced open-angle glaucoma. Lee et al [46] evaluated correlations between neuroretinal rim area rates of change and VF rates of change in glaucoma patients with a wide range of glaucoma severity and found that a decreased rim area correlated with a worse MD and the mean threshold sensitivities of fast components of VF decay in moderate/advanced glaucoma.…”
Section: Discussionmentioning
confidence: 99%
“…Changes in ONH parameters, such as the rim area and C:D ratio (average and vertical), were small but statistically significant in advanced glaucoma [15]. Kostianeva et al [45] found significant correlations of the rim area and C:D ratio with the HFA 30-2 VF MD in advanced open-angle glaucoma. Lee et al [46] evaluated correlations between neuroretinal rim area rates of change and VF rates of change in glaucoma patients with a wide range of glaucoma severity and found that a decreased rim area correlated with a worse MD and the mean threshold sensitivities of fast components of VF decay in moderate/advanced glaucoma.…”
Section: Discussionmentioning
confidence: 99%
“…4,[8][9][10] Although attempts have been made to identify the associations between structural measures and functional defects in glaucoma, the structurefunction relationship in advanced glaucoma has not been thoroughly investigated. 8,[11][12][13] Recently, we evaluated the relationship between the central VF and macular parameters in advanced glaucoma patients whose peripapillary RNFL thickness reached the measurement floor and found that the nasal macular region showed statistically significant relationships with the central VF. In addition, we found some differences in the structure-function relationship between primary open angle glaucoma (POAG) and normal-tension glaucoma (NTG) patients.…”
mentioning
confidence: 99%
“…Specifically, the strength of the structure-function relationship is known to be weaker in the early stage of glaucoma and reaches its peak in the moderate stage, after which it gradually decreases as the disease progresses to the advanced stage 4,8–10. Although attempts have been made to identify the associations between structural measures and functional defects in glaucoma, the structure-function relationship in advanced glaucoma has not been thoroughly investigated 8,11–13. Recently, we evaluated the relationship between the central VF and macular parameters in advanced glaucoma patients whose peripapillary RNFL thickness reached the measurement floor and found that the nasal macular region showed statistically significant relationships with the central VF.…”
mentioning
confidence: 99%